Assessing resilience in long-term ecological data sets. (June 2016) - Müller, F.; Bergmann, M.; Dannowski, R.; Dippner, J.W.; Gnauck, A.; Haase, P.; Jochimsen, Marc C.; Kasprzak, P.; Kröncke, I.; Kümmerlin, R.; Küster, M.; Lischeid, G.; et al.
Highlights: The occurrence of resilience strongly coincides with short-term dynamics. Adaptability is found mainly in long-term data sets. In all case studies several disturbances with different operational scales were interlinked. Abstract: In this paper the concept of resilience is discussed on the base of 13 case studies from the German branch of the International Long-Term Ecological Research Program. In the introduction the resilience approach is presented as one possibility to describe ecosystem dynamics. The relations with the concepts of adaptability and ecological integrity are discussed and the research questions are formulated. The focal research objectives are related to the conditions of resilient behaviour of ecosystems, the role of spatio-temporal scales, the differences between short- or long-term dynamics, the basic methodological requirements to exactly define resilience, the role of the reference state and indicators and the suitability of resilience as a management concept. The main part of the paper consists of 13 small case study descriptions, which demonstrate phase transitions and resilient dynamics of several terrestrial and aquatic ecosystems at different time scales. In the discussion, some problems arising from the interpretation of the time series are highlighted and discussed. The topics of discussion are the conceptual challenges of the resilience approach, methodological problems, the role of indicator selection, the complex interactions between different disturbances, the significance of time scales and a comparison of the case studies. The article ends with a conclusion which focuses on the demand to link resilience with adaptability, in order to support the long-term dynamics of ecosystem development.